Corporate Venture Sector: The Problem of Staffing - V. G. Zinov; D. V. Kozlov (Ekonomika Nauki)
The problem of staffing in innovation management is one of the main resources of the modern Russian economy. Based on the data of the Ministry of Education and Science of Russia, in-depth interviews with representatives of large companies, and government authorities, the authors attempted to identify the most relevant and popular approaches to solving the problem of staffing the venture capital industry in the corporate sector. The article defines the general vector of development of the corporate venture capital sector in Russia, analyzes the contribution of universities and large companies to the creation of a talent pool. It is concluded that universities do not cover the need for training highly qualified personnel for innovation management, while large companies are building up competencies in the field, using and using effective training tools for working with venture projects.